INTERACTION OF VERBAL AND NONVERBAL COMMUNICATION MEANS IN THE FRENCH LANGUAGE - Hayatova Nigina Ikromjonovna (Bright Mind Publishing, 2025)
This article analyzes the interaction of verbal and nonverbal means of communication, highlighting their significance in interpersonal interaction. The first section examines verbal means such as vocabulary, grammar, and intonation, as well as their impact on the comprehension of messages. The second section focuses on nonverbal means, including gestures, facial expressions, posture, and the use of space. The author emphasizes how these two types of communication means complement each other, forming a more complete perception of the speaker’s intentions and emotions. Cultural differences in the interpretation of nonverbal signals and their role in effective communication are also discussed.
Keywords: Verbal communication, nonverbal communication, gestures, facial expressions, intonation, interpersonal interaction, paralinguistics, proxemics, cultural differences.